2010
DOI: 10.17161/str.1808.10073
|View full text |Cite
|
Sign up to set email alerts
|

White Means Never Having to Say You're Sorry The Racial Project in Explaining Mass Shootings

Abstract: Mass shootings, such as the ones that occurred at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…37 – 39 By contrast, race and ethnicity often play a key role in accounts of mass shootings when the perpetrator is not white. For example, after the 2007 mass shooting at Virginia Tech University perpetrated by a college student of Korean-American heritage, media outlets reported that Asian-Americans experienced fear of retaliation and felt forced to issue an apology on behalf of their “group.” 40 …”
Section: An Agenda For Mental Health Research Into Mass Shootings Andmentioning
confidence: 99%
“…37 – 39 By contrast, race and ethnicity often play a key role in accounts of mass shootings when the perpetrator is not white. For example, after the 2007 mass shooting at Virginia Tech University perpetrated by a college student of Korean-American heritage, media outlets reported that Asian-Americans experienced fear of retaliation and felt forced to issue an apology on behalf of their “group.” 40 …”
Section: An Agenda For Mental Health Research Into Mass Shootings Andmentioning
confidence: 99%
“…They find an emphasis on the shooter's ethnicity, in contrast with coverage of Columbine, where the white shooter's racial background was less highlighted. Similarly, Mingus and Zopf (2010) observe that for four mass shootings, across a variety of news sources, the race of minoritized perpetrators is emphasized, while the race of white shooters is often omitted.…”
Section: Nationality Race Ethnicity and Religionmentioning
confidence: 96%
“…Scholars have attempted to apply the racial project to important fields such as: education, the media, religion, and cultural studies (Staiger 2004;Alumkal 2004;Mingus and Zopf 2010;Brooms 2014). All of these fields play a role in our daily lived experiences, and all of them represent a racial project in some way.…”
Section: Racial Projects: Discussion and Relevancementioning
confidence: 99%